Mathematical model of a medical waste thermal treatment plant - Bujak, Janusz; Majkowski , Sebastian (Instal, 2019)
This paper presents a mathematical model of a thermal waste management plant with an energy recovery system, including energy flow balance and mass flow balance. This mathematical model enables determination of thermal and electrical operating efficiency of similar plants. The mathematical model conceived herein enables evaluation of individual components for system efficiency at the stage of plant design and operation. The waste thermal treatment plant (hereinafter referred to as WTTP) consists of a waste preparation and loading unit, a rotary kiln, a thermoreactor chamber, a steam recovery boiler, a steam turbine, and a system recovering heat as hot water. Verification of the mathematical model involved a system with a rotary kiln and an afterburner chamber in continuous operation with a throughput of 150 kg/h.